Changes in inflammatory mediators as a result of intermittent hypoxia in obstructive sleep apnea syndrome. (23rd November 2017) - Sozer, Volkan; Kutnu, Müge; Atahan, Ersan; Calıskaner Ozturk, Buket; Hysi, Ergi; Cabuk, Cansu; Musellim, Benan; Simsek, Gonul; Uzun, Hafize
Abstract: Background: Inflammation plays an important role in obstructive sleep apnea syndrome (OSAS). The objective of this study was to investigate the relationship of serum C‐reactive protein (CRP), pentraxin‐3 (PTX‐3), procalcitonin (ProCT), interleukin‐33 (IL‐33) and its soluble receptor ST2 (sST2) with the syndrome severity and to show theirs importance as biomarkers. Methods: This study comprises a total of 84 identical (sex and age wise) cases. Full‐night polysomnography was performed in each patient. OSAS diagnosis and severity index being based on the widely used criterion known as Apnea Hypopnea Index(AHI). Subgroups were as follows: 24(AHI < 5) controls, 28 mild‐moderate OSAS(AHI 5–30) and 32 severe OSAS(AHI > 30). Results: PTX‐3, IL‐33 and sST2 receptors were significantly higher in OSAS groups than the control group ( P < .001). However, both CRP and ProCT levels were similar in all subjects. There was a positive correlation between PTX‐3 and BMI ( r = 0.446; P < .01), ODI ( r = 0.555; P < .01), IL‐33 ( r = 0.348; P = .001) and sST2 ( r = 326; P = .002), while there was a negative correlation with minimum SaO2 ( r = −0.672; P < .01) in patient group. PTX‐3 as a predictor of OSAS showed highest specificity (%91.7) and sensitivity (%91.7) ( P < .001). Conclusions: PTX‐3 can be a new indicator reflecting the inflammatory state in patients with OSAS. Since patients with OSAS could have more hypoxic state during sleep, we found higher PTX‐3 level in those patients and a negative correlation between PTX‐3 and minimum SaO2, which could explain that PTX‐3 levels can increase with the severity of disease. Our results suggest that PTX‐3 as an inflammatory biomarker may play a crucial role as an indicator of syndrome severity in OSAS.